Canny and Gauss Enhancement on Speckle Reducing Anisotropic Diffusion - Uslu, Erkan; Albayrak, Songul (IEEE, 2013)
In this work speckle reduction methods defined in the literature are basically compared according to effect on classification, edge preservation and noise reduction in homogenous regions. The methods are tested on labeled SAR image, simulated SAR image and optical image. It is aimed to present mutual effect of speckle reduction methods on both edge preservation and noise reduction. One of the purposes of this work is to improve SRAD method, which is especially defined for speckle noise reduction, by combining it with Canny edge detection and Gauss filtering. It is proved by the experimental results that proposed method enhances the quality measure results.
Keywords: Speckle noise reduction; Speckle Reducing Anisotropic Diffusion (SRAD); Canny edge detection enhanced SRAD; Gauss filter enhanced SRAD; Engineering; Telecommunications